STRATEGIC MANAGEMENT MODEL FOR MICRO AND SMALL SNACK FOOD BUSINESS PERFORMANCE EVALUATION - Rakhma Oktavina (Jurnal Ilmiah Ekonomi Bisnis, 2009)
The main problems in developing snack small and medium enterprises include incompetency in optimizing their resources and in maintaining their business environments. These result in low of productivity, quality, and competitiveness. Accordingly, an evaluation on self condition and their environment in relation to decision making process towards snack small and medium enterprises development policy through performance measurement and improvement is required. Balanced Scorecard was used in measuring firm performances. OWA Operator was performed in assigning key performance indicators (KPI or IKK). Perspective weight, KPI, and target were assigned using Fuzzy AHP. Steps of performance improvement was developed on three submodels: (1) submodel of identification of customers’ needs and technical characteristics, (2) submodel of assigning importance weight of customers needs, correlations among technical characteristics, and value of relationship between customers importance and technical characteristics, and (3) submodel of assigning priority and recommendation for performance improvement. Model verification was applied on banana crackers small and medium enterprises. OWA Operator techniques was used to generate 10 alternatives of technical characteristics assigning importance weight of customers, correlations among technical characteristics, and value of relationship between customers importance and technical characteristics. Quality Function Deployment (QFD) technique was used to assign priority andrecommendation for performance improvement. The developed model was implemented to generate performance improvement recommendation of banana crackers small and medium enterprises in Bandar Lampung, Province of Lampung.Key words: banana crackers small and medium enterprises; performance evaluationmodel; strategic management systems.